Social aspects of tourism policy in the European Union.: The example of Poland and Slovakia - Aleksander Panasiuk; Ewa Wszendybyl-Skulska (Economies, 2021)
Since the beginning of the 21st century, the European Union tourism policy has been increasingly focused on initiatives in the field of social tourism, which are one of the ways of achieving sustainable development in the European tourism economy. Most of the research projects that have so far been conducted in the field have focused on the benefits for its participants (subjective one: Children and youths, seniors, disabled people, people (families) with low incomes and/or unemployed, big families). However, there is a lack of research on the analysis of the place of social aspects of tourism in the general socio-economic policy of the state and, in a detailed aspect, in the sectoral policy represented by tourism policy, as well as its potential impact on the development of the national economy and meeting tourism needs of the society. The authors tried to fill this research gap in this study. The aim of the study is to differentiate the issues related to the social aspects of tourism policy from the entire socio-economic policy pursued in the European Union and selected member states (Poland and Slovakia). The article is of a theoretical-analytical-conceptual nature. Empirical research, due to the nature of its issues, was conducted with the use of qualitative research methods. The results of the conducted research showed that activities in the field of social tourism policy are conditioned by organizational solutions for the entities that undertake them, as well as economic ones, especially in the field of financing. Moreover, they made it possible to propose the concept of a model social tourism policy with an indication of its place in the European policy on the basis of the past and future EU financial perspectives.
Keywords: 330; socio-economic policy; tourism economy; tourism policy; social tourism; European Union; Poland; Slovakia